Gastrointestinal stromal tumors with BRAF gene fusions. A report of two cases showing low or absent KIT expression resulting in diagnostic pitfalls. Issue 12 (25th August 2021) - Torrence, Dianne; Xie, Ziyu; Zhang, Lei; Chi, Ping; Antonescu, Cristina R.
Abstract: Although most gastrointestinal stromal tumors (GISTs) exhibit activating mutations in either KIT or PDGFRA, rare cases have shown to be driven by gene fusions involving kinases, mainly involving NTRK3, and rarely BRAF or FGFR1 . BRAF gene rearrangements have been described in only two patients to date, as separate case reports. In addition, BRAF V600E mutation is an uncommon but established oncogenic pathway in GIST. In this report, we describe two new GIST cases harboring novel BRAF fusion genes, arising in two young‐adult women (37 and 40 years of age) in the small bowel and distal esophagus, both with a spindle cell phenotype. The small bowel GIST measured 2.8 cm and showed a high cellularity and a mitotic rate of 20/50 HPFs, while the esophageal lesion measured 7 cm and 1/50 HPFs. Immunohistochemically, both tumors showed diffuse reactivity for DOG1, while KIT/CD117 was weakly positive in the small bowel GIST and completely negative in the esophageal tumor. Based on these findings, the latter case was misinterpreted as a low‐grade myxoid leiomyosarcoma, as it showed a myxoid stroma, reactivity for SMA and focal positivity for desmin. Archer FusionPlex revealed a fusion between BRAF with either AGAP3 or MKRN1 gene partners. Moreover, MSK‐IMPACT DNA targeted sequencing confirmed both fusions but did not identify additional mutations. In one case with available material, the BRAF gene rearrangement was also validated by FISH. The recognition of BRAF fusion‐positive GISTs is critical as it may be associated with a low level of KIT expression and may result in diagnostic challenges with significant impact on therapeutic management. The clinical benefit with KIT inhibitors, such as imatinib, remains to be determined.